2019
DOI: 10.21061/jvs.v4i2.119
|View full text |Cite
|
Sign up to set email alerts
|

Toward Veteran-Centered Research: A Veteran-Focused Community Engagement Project

Abstract: Although it is widely acknowledged that consumer engagement in healthcare research is a promising pathway to actionable patient-centered findings, there remains some ambiguity regarding effective patient-centered engagement strategies. Therefore, the purpose of this US-based multi-state project was to create a platform from which US veterans could dialogue and articulate (1) their research priorities; (2) perceived barriers to research partnerships and participation; (3) recommendations for engaging other vete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Community engagement activities, such as gatherings and town halls, provide platforms for invested parties to have an active voice. Innovative community engagement approaches hold the potential to generate socially relevant and applicable research findings (Flynn, Krause-Parello et al, 2019). These methods can establish partnerships around significant clinical and social problems, such as community prevention of veteran suicide, that have not been effectively addressed by traditional randomized controlled trial (RCT) designs.…”
Section: Methodsmentioning
confidence: 99%
“…Community engagement activities, such as gatherings and town halls, provide platforms for invested parties to have an active voice. Innovative community engagement approaches hold the potential to generate socially relevant and applicable research findings (Flynn, Krause-Parello et al, 2019). These methods can establish partnerships around significant clinical and social problems, such as community prevention of veteran suicide, that have not been effectively addressed by traditional randomized controlled trial (RCT) designs.…”
Section: Methodsmentioning
confidence: 99%
“…Engaging patients and consumers in healthcare research has the potential to create meaningful interventions, yet there is a well-recognized reluctance among veterans to participate in patient-centered research. This reluctance stems from an unfamiliarity and distrust of the research process (Flynn & Krause-Parello, 2019). Evaluation of this project suggests that participation in the VDRPTP may reduce veterans' concerns about safety and privacy when participating in research.…”
Section: Implications For Clinical Practice Public Policy or Future Researchmentioning
confidence: 99%
“…Our previous engagement projects confirmed that many veterans are unfamiliar with the research process and are uncomfortable embracing the role of research partner. Operation PCOR was designed based on veterans' expressed concerns and recommendations elicited from our previous engagement projects (Flynn et al, 2019;Krause-Parello, et al, 2019). Therefore, the overarching goal of this current project was two-fold: 1.…”
Section: Rationale Informing the Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…This veteran-driven community engagement enhancement project built upon successful methods developed during prior patient engagement projects (Flynn et al, 2019). Building on our previous research and community engagement work, the objectives of this enhancement project were to: (a) describe dilemmas and health management challenges facing veterans and key community stakeholders during the COVID-19 pandemic; (b) provide veteran and stakeholder recommendations for successful approaches to resolving those dilemmas, (c) increase veterans' capacity for social engagement during times of social isolation, and (d) increase veterans' capacity for research engagement across all phrases of patient-centered outcomes research (PCOR) and comparative effectives research (CER) projects.…”
Section: Project Structure/proceduresmentioning
confidence: 99%